Characteristic of encapsulat pandanus fruit dye extract on the type and concentration of encapsulant - Wartini, Ni Made; Putra, G.P. Ganda (Media Ilmiah Teknologi Pangan (Scientific Journal of Food Technology); Vol 5 No 2 (2018): Scientific Journal of Food Technology (September), 2018)
Pandanus fruit that is yellow to orange can be used as a food coloring as well as a source of pro vitamin A. Food coloring from pandanus extract is made in powder form for easier use and more stable in storage. The purpose of this research is to determine the best encapsulan type and concentration to produce pandanus fruit color extract encapsulat. The main ingredients of the research are yellow to orange pandanus, acetone, chloroform, maltodextrin, and gum arab. The experiment was a two-factor factorial experiment using randomized block design. The first factor is encapsulation (maltodextrin and gum arab), second factor is concentration of encapsulan solution (10, 20, 30%). Prepared a powder 60 mesh with water content of about 8-10%, then extracted with chloroform acetone solvent (1: 3), at 50 ° C, for 5 hours, resulting in extracts of thick pandanus color. The thick pandanus colorant extract was encapsulated using maltodextrin and gum arab respectively with concentrations of 10, 20, and 30%. The results showed that the best encapsulan type and concentration to produce pandanus fruit extract encapsulat was 10% gum arabic with water content characteristic 9.40 ± 2.01%, solubility 92.57 ± 0.63%, total carotenoid 18.78 ± 1.78 mg / 100g, surface carotenoid 0.04 ± 0.03 mg / 100g, encapsulation efficiency 99.88 ± 0.09%, brightness, redness, and yellowish levels of 28.53, 8.67, and 45.39 respectively.